The differentiated impacts of organizational innovation practices on technological innovation persistence. Issue 1 (12th January 2015) - Le Bas, Christian; Mothe, Caroline; Nguyen-Thi, Thuc Uyen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to test the major determinants of technological (product and process) innovation persistence and provides evidence of the significant role of organizational innovation. Design/methodology/approach – Data came from two waves of the Luxembourg Community Innovation Survey (CIS): CIS2006 for 2004-2006 and CIS2008 for 2006-2008. The longitudinal data set resulted in a final sample of 287 firms. A multinomial probit model estimates the likelihood that each firm belongs to one of three longitudinal innovation profiles: no, sporadic, or persistent innovators. Findings – The determinants have differentiated impacts on process and technological innovation persistence. Organizational innovation influences technological innovation persistence. In the analysis of detailed organizational practices, strong evidence emerged that knowledge management exerts a crucial effect on product innovation persistence; workplace organization instead is associated with process innovation persistence. Research limitations/implications – The relationships of innovation persistence, organizational innovation, and firms' economic performance demand further exploration. The different persistence patterns of complex (process and product) and simple (process or product) innovators also are worth investigating. Practical implications – Organizational innovation matters for technological innovation persistence. However, the effects of non-technological innovation differ depending on whether the firm wants to innovate in processes or products. Managers must acknowledge these various effects and select appropriate strategies. Originality/value – Few works account for the impact of organizational innovation strategies on technological innovation. This study is the first, based on recent CIS data, to address the role of organizational innovation practices for technological innovation persistence, which appears necessary for the sustainable dynamics of firms, industries, and regions.